She Did It! - Ericsson, Jennifer A. (New York : Melanie Kroupa Books/Farrar Straus Giroux, 2002)
Four busy sisters make a mess while eating and playing, and each one blames the others when their mother gets angry.
Keywords: Sisters -- Fiction; Stories in rhyme